Knowledge and practice of colorectal cancer screening in an urban setting: cross-sectional survey of primary care physicians in government clinics in Malaysia - Ooi, Chor Yau; Hanafi, Nik Sherina; Liew, Su May (Stamford Publishing Pte Ltd / Singapore Medical Association, 2019)
INTRODUCTION Colorectal cancer (CRC) was the third most commonly diagnosed cancer worldwide in 2008 (1.23 million cases, 9.7%). CRC screening was shown to be effective in reducing 70% of CRC mortality. However, the screening rate for CRC remains poor. METHODS A cross-sectional survey was conducted among primary care physicians (PCPs) in public primary care clinics in Kuala Lumpur, Malaysia. A 30-item self-administered questionnaire was used to assess the knowledge and practice of CRC screening. RESULTS The response rate was 86.4% (n = 197/228). Less than half (39.1%) of the respondents answered correctly for all risk stratification scenarios. Mean knowledge score on CRC screening modalities was 48.7% ± 17.7%. The knowledge score was positively associated with having postgraduate educational qualification and usage of screening guidelines. Overall, 69.9% of PCPs reported that they practised screening. However, of these, only 25.9% of PCPs screened over 50% of all eligible patients. PCPs who agreed that screening was cost-effective (odds ratio [OR] 3.34, 95% confidence interval [CI] 1.69-6.59) and those who agreed that they had adequate resources in their locality (OR 1.92, 95% CI 1.01-3.68) were more likely to practise screening. Knowledge score was not associated with the practice of screening (p = 0.185). CONCLUSION Knowledge and practice of CRC screening was inadequate among PCPs. Knowledge of screening did not translate into its practice. PCPs' perceptions about cost-effectiveness of screening and adequate resources were important determinants of the practice of screening. © 2019 Singapore Medical Association. All rights reserved.